Extreme heat alters the performance of hosts and pathogen - Porras, Mitzy F.; Navas, Carlos A.; Agudelo-Cantero, Gustavo A.; Santiago-Martínez, Michel Geovanni; Loeschcke, Volker; Sørensen, Jesper Givskov; Crandall, Sharifa G.; Biddinger, David; Rajotte, Edwin G. (Frontiers in Ecology and Evolution, 2023)
The frequency and intensity of extreme heat in the environment have increased in the last decade. Extreme heating events (EHE) have wide-ranging impacts on biological systems from the molecular to the community level. However, the impacts of EHE have been poorly studied in pathogen-host systems. Here, we explore how EHE affects the interaction among the insect hosts, Osmia cornifrons and O. lignaria, and a protozoan pathogen, Crithidia mellificae. Our results showed that 1-day EHE significantly reduced the upper limit for locomotion of hosts by an average of 4 °C in healthy and 7 °C in infected hosts. Further, EHE significantly reduced the protozoan pathogen growth rate. EHE also reduced the hosts’ voluntary exposure to (or transit across) extreme (hot or cold) temperature zones (ETZ). Our results show that EHE reduces both hosts’ heat tolerance and pathogen fitness, and shed light on the implications of EHE on host-pathogen dynamics under warmer world.